Occurrence of guggulsterone content based chemotypes in Commiphora wightii - Haque, Inamul; Mukhopadhyay, Kunal (Current Botany, 2024)
Commiphora wightii is a critically endangered plant endemic in the arid and semi-arid regions of India. Oleogum is produced by the plant schizogenously. Upon making an incision, this gum exudes from the wound and solidifies in the arid environment. This solidfied gum-resin called ‘gum guggul or guggal’ is mentioned in Ayurvedic, Unani and Siddha literature for the treatment of many ailments. The steroidal ketones, E- and Z- guggulsterone are believed to be the active principles responsible for the medicinal properties. These resin samples were collected from plants in a few regions of Rajasthan, India, for quantitation of guggulsterone content using HPLC. Based on the quantitation of the guggulsterone content, we were able to identify three chemotypes. The first and the most common chemotype showed relatively much higher Z-guggulsterone than E-guggulsterone, the second type showed the absence of E-guggulsterone, the third and rare type showed the presence of equal amounts E- and Z-guggulsterone.